Is the recall of men who have sex with men (MSM) diagnosed as having bacterial sexually transmitted infections (STIs) for re-screening a feasible and effective strategy?. Issue 7 (28th September 2011) - Harte, Derval; Mercey, Danielle; Jarman, Jay; Benn, Paul
Abstract : Objectives: To assess the feasibility and outcomes of recalling men who have sex with men (MSM) diagnosed as having a bacterial sexually transmitted infection (STI) for re-screening. Methods: This evaluation was conducted from December 2008 for a 9-month period. MSM diagnosed as having a bacterial STI in that period were offered recall for re-screening 3 months after their diagnosis. Re-screening rates and infection incidence were calculated. Differences in baseline characteristics by re-screening status and factors predictive of infection at re-screening were assessed using the Mann–Whitney test, χ 2 test and logistic regression. Results: Of the 337 MSM diagnosed as having a bacterial STI, 301 were offered recall. Of these, 206 (68.4%) re-screened after 3 months, 30 (10%) declined and the remainder did not re-attend despite giving verbal consent. Compared with those not re-screening, those re-screening were less likely to be HIV positive (p=0.001), but there was no difference in baseline risk behaviours. There were 15 diagnoses of bacterial STIs at re-screening (29 per 100 person-year follow-up (pyfu); 95% CI 14.3 to 43.7) and five new HIV diagnoses of whom three had a negative test at baseline, one tested negative 6 months earlier and one never tested. Among those testing at both time points, the HIV incidence was 8.3 per 100 pyfu (95% CI 0.0 to 17.7). Conclusions: This evaluation demonstrates a 'recall for re-screening' strategy is feasible in terms of high re-screening rates and incidence of new infections diagnosed. Experimental evidence is needed to assess cost-effectiveness and whether it achieves its aim of reducing transmission of STIs and HIV.